Use of biologic agents and risk of tuberculosis in Brazil, a tuberculosis high-burden country - Fernanda Gomes Gonçalves Chaer; Juliana Miranda de Lucena Valim; Rogério Castro Reis; Giselle Burlamaqui Klautau; Branca Dias Batista de Souza (BioExcel Publishing Ltd, 2020)
Background: Brazil is a country with a high burden of tuberculosis (TB). The immunomodulatory effect of biological therapies is associated with an increased risk of infection. This study evaluated the frequency of TB infection in patients with rheumatoid arthritis (RA), ankylosing spondylitis (AS), juvenile idiopathic arthritis (JIA), and psoriatic arthritis (PsA) after the use of biologic agents in a single center of rheumatology. Methods: In this observational study, 161 consecutive adult patients with RA, JIA, AS, and PsA using biological therapy were followed up during 55 months to evaluate the occurrence of TB infection throughout treatment. All patients were screened for latent TB infection (LTBI), and TB disease was excluded before introduction of biological therapy. Patients with LTBI received prophylaxis with isoniazid before the start of biological treatment. Results: Of 161 patients on biologics, 31 (19.25%) had positive tuberculin skin test (TST) and received LTBI treatment. Eleven (6.8%) cases of TB were detected in patients on biologics, six (54.5%) had AS, one had PsA (9.09%), two had RA (18.18%), and two had JIA (18.18%). Regarding the use of different biologics, six (54.5%) patients received adalimumab, three (27.2%) infliximab, one (9.09%) etanercept, and one (9.09%) tocilizumab. Conclusion: In this study, the frequency of TB infection among 161 patients on biologics, during 55 months of follow-up, was 6.8%. Compared with the national registry of patients receiving biologics (BiobadaBrasil - January 01, 2009 to May 31, 2013), a higher incidence of TB (6.8 versus 0.44%) was found in this sample of patients receiving biological therapy. This study highlights that in a country with high TB burden, the possibility of TB infection in a patient receiving biological therapy should always be considered, even after prophylaxis with isoniazid.